Anti-glucan effects of propolis ethanol extract on Lactobacillus acidophillus - Ira Widjiastuti; Adioro Soetojo; Febriastuti Cahyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: In deep dentinal caries cases, bacteria mostly found are Lactobacillus acidophilus classified as gram positive bacteria and as facultative aerobes producing glucosyltransferase (GTF) enzyme. GTF enzyme can alter sucrose into glucans. Glucan is sticky and insoluble in water. As a result, GTF enzyme can facilitate plaque formation and microorganism colonization on tooth surface. In addition, Lactobacillus acidophilus also can form acid leading to demineralization of organic and inorganic materials, resulting in dental caries. Multidrug-resistant phenomena, on the other hand, have led to the use of natural resources, one of which is propolis as an antimicrobial material and as a new anti-infective therapeutic strategy. Propolis is a resinous substances collected by worker bees (Apismellifera) from barks and leaves of plants. Propolis has a complex chemical composition and biological properties, such as antibacterial, antiviral, antifungal, anti-inflammatory, and antitumor. Purpose: This research aimed to reveal anti-glucan effects of propolis ethanol extract generated from honey bee, Apis mellifera spp on Lactobacillus acidophilus bacteria. Method: Before antiglucan test was conducted, glucan-formation test was performed on Lactobacillus acidophilus bacteria using SDSpage. Meanwhile, anti-glucan adhesion test on Lactobacillus acidophilus bacteria was carried by culturing the bacteria at 37ºC temperature in a jar with 10% CO2. Test tubes were placed at an angle of 30º for 18 hours to review the attachment of bacteria at the glass surfaces. After the incubation, the culture of bacteria was vibrated using a mixer vortex for a few minutes, and then cultured in solid MRS A media. Bacteria grown were measured by using colony counter. Result: The ethanol extract of propolis with a concentration of 1.56% was the lowest concentration inhibiting the attachment of glucan to Lactobacillus acidophilus bacteria. Conclusion: The ethanol extract of propolis with a concentration of 1.56% can be used as an anti-glucan material for Lactobacillus acidophilus bacteria.